IMPLEMENTASI MANAJEMEN BERBASIS BUDAYA RELIGIUS DALAM PENINGKATAN MUTU PENDIDIKAN DI SMK DARUL ULUM BANYUPUTIH - Idzi Layyinnati (Nusantara Journal of Islamic Studies, 2023)
This study focuses on the implementation of religious culture-based management in improving the quality of education at SMK Darul Ulum Banyuputih with the following problem formulations: (1) How is the implementation of religious culture-based management in improving the quality of education at SMK Darul Ulum Banyuputih? (2) What are the supporting and inhibiting factors for the implementation of religious culture-based management in improving the quality of education at SMK Darul Ulum Banyuputih? This study aims to describe both of these things. To achieve these goals, this study uses a qualitative approach with a descriptive method research type. Data collection techniques are carried out using observation, interview, and documentation techniques. The collected data are interpreted and analyzed by reducing data, presenting data, and drawing conclusions. The results of the study indicate that the reality of religious culture at SMK Darul Ulum Banyuputih includes: 5S (smile, greeting, greeting, polite, courteous), implementation of congregational dhuha prayer, habituation of reciting asmaul husana, memorizing the Qur'an, inspirational stories. The implementation of religious culture can influence the implementation of high-quality education and the formation of positive attitudes and morals for all students in educational institutions.